2021
DOI: 10.1080/07853890.2021.1968027
|View full text |Cite
|
Sign up to set email alerts
|

The high platelet counts as predictor for early foetal demise

Abstract: Objectives: Early fetal demise (absence of cardiac activity in a visible fetus) is a very common event, but there are no reliable biomarkers to predict it. The purpose of the study was to assess the association of platelet parameters with early fetal demise. Methods: In this case-control study, we included women with normal deliveries or those ultrasound diagnosed as early fetal demise. For those who were identified with early fetal demise, the platelet parameters were analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…They found that platelet counts were significantly higher in pregnant women with miscarriage compared to healthy pregnancies, and high platelet count was independently associated with an increased risk of miscarriage. 18 Therefore, the platelet count may be the reason of significant results for SII. The SII incorporates lymphocyte, neutrophil, and platelet parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that platelet counts were significantly higher in pregnant women with miscarriage compared to healthy pregnancies, and high platelet count was independently associated with an increased risk of miscarriage. 18 Therefore, the platelet count may be the reason of significant results for SII. The SII incorporates lymphocyte, neutrophil, and platelet parameters.…”
Section: Discussionmentioning
confidence: 99%
“…It also has functions in maternal‐fetal vascular remodeling 17 . Shao et al 18 evaluated the platelet counts of 99 women with miscarriage at 5–10 weeks of gestation and 170 pregnant women with an uncomplicated pregnancy. They found that platelet counts were significantly higher in pregnant women with miscarriage compared to healthy pregnancies, and high platelet count was independently associated with an increased risk of miscarriage 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Researchers discovered that pregnant women experiencing a miscarriage had much higher platelet counts compared to those in healthy pregnancies. Moreover, a high platelet count was revealed to be independently related with an increased risk of miscarriage [16]. The levels of CA125 are significantly different between the two sets of data (aborted and not aborted).…”
Section: Discussionmentioning
confidence: 93%
“…An analogous study by Shao et al (2021) compared the platelet counts of 170 healthy pregnant women to those of 99 women who had a miscarriage between 5 and 10 weeks into their pregnancies. A high platelet count was shown to be independently related with an increased risk of miscarriage [16], and it was also considerably greater in pregnant women who had miscarriages compared to healthy pregnancies. The two groups' CA125 levels varied significantly from one another (aborted and not aborted).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the platelet activation of pregnant women with preeclampsia, fetal growth restriction, and preterm birth is higher than that of normal pregnant women and nonpregnant women ( 28 30 ). Increased platelet counts in the first trimester were suggested to be useful in predicting of early fetal demise ( 31 ). Our study also found that platelets were higher in pregnant women in the adverse neonatal outcome group.…”
Section: Discussionmentioning
confidence: 99%